Ecologia trófica de anfíbios anuros: relações filogenéticas em diferentes escalas - Amado, Talita Ferreira (2014)
Understand the origin, maintenance and the mechanisms that operate in the current biodiversity is the major goal of ecology. Species ecology can be influenced by different factors at different scales. There are three approaches about the ecological differences between species: the first brings that differences result from current processes on niche characteristics (e.g. diet, time, space); the second that species differences are explained by random patterns of speciation, extinction and dispersion, the third that historical events explain the formation and composition of species in communities. This study aims to evaluate the influence of phylogenetic relationships in determining ecological characteristics in amphibians (globally) and test with that, if ecological differences between species of frogs are the result of ancient pre-existing differences or as result of current interactions. Another objective of this study is to verify if ecological, historical or current characteristics determine the size of species geographical distribution. The diet data for analysis of trophic ecology were collected from published literature. We performed a non-parametric MANOVA to test the existence of phylogenetic effects in diet shifts on frogs history. Thus, it is expected to know the main factors that allow the coexistence of anuran species. We performed a phylogenetic regression to analyze if niche breadth, body size and evolutionary age variables determine the size of the geographical distribution of amphibians in the Amazon. In the present study, new contributions to knowledge of major ecological patterns of anurans are discussed under a phylogenetic perspective